Theoretical explanation of brand rejuvenation: a substantive theory - Villegas, Juliana (Pontificia Universidad Católica del Perú, 2019)
The purpose of this research study that uses a qualitative approach was to propose an intermediate theory using the Grounded Theory, that would theoretically explain the brand rejuvenation phenomenon. To do this, several criteria were defined that lead to a sample of 18 brands that had undergone a rejuvenation process. As sources of evidence, in depth interviews were held with senior executives that participated in the branding work, as well as a documentary review of the rejuvenation process for each of these brands, an in-depth literature review and an evaluation by 10 experts who compared the aging brand and the rejuvenated brand for each of the 18 cases. After interpreting the primary and secondary data using the Atlas Ti 8 software and comparing its results with scattered knowledge found in the literature review, an intermediate theory emerged, that responded to the study’s questions on three topics: The symptoms of brand aging, the brand rejuvenation intervention process, and the results of brand rejuvenation. This allowed concluding that, to explain the brand rejuvenation process, it is necessary to go back to its causes, understand its motivators and purposes, implement a process for planning, executing and evaluating the rejuvenation phenomenon, and investigating its results. A step-by-step process was also identified that explains how the brand rejuvenation process occurs and that accounts for the reversal of the brand aging process. It was reaffirmed that brand rejuvenation is necessary because it responds to different requirements of the environment, of the firm and to certain strategic marketing goals. Proposals for future studies include proving, quantitatively, the 16 propositions put forward in this research study that provide a theoretical explanation for brand rejuvenation. Another suggestion is to expand the scope with failed cases, other brand taxonomies, or a review of the phenomenon from a demand perspective.
Keywords: Marcas de fábrica; Comportamiento del consumidor; Investigación cualitativa; https://purl.org/pe-repo/ocde/ford#5.02.04